2022
DOI: 10.3390/cancers14010248
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Priming with Decitabine Augments the Therapeutic Effect of Cisplatin on Triple-Negative Breast Cancer Cells through Induction of Proapoptotic Factor NOXA

Abstract: Epigenetic alterations caused by aberrant DNA methylation have a crucial role in cancer development, and the DNA-demethylating agent decitabine, is used to treat hematopoietic malignancy. Triple-negative breast cancers (TNBCs) have shown sensitivity to decitabine; however, the underlying mechanism of its anticancer effect and its effectiveness in treating TNBCs are not fully understood. We analyzed the effects of decitabine on nine TNBC cell lines and examined genes associated with its cytotoxic effects. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Decitabine increased cisplatin's NOXA-mediated pro-apoptotic effect on breast cancer cell lines, demonstrating decitabine's good clinical potential in combination with cisplatin for the treatment of triple-negative breast cancers. 84 It has been shown that mitochondrial DNA depletion and low mitochondrial membrane potential can induce DNA methylation via DNMT and that zebularine inhibits epithelial–mesenchymal transition and improves chemotherapy sensitivity in mitochondrial DNA-depleted esophageal cancer cells. As a result, therapeutic strategies that increase the copy number of mitochondrial DNA and DNMT inhibitors may be useful in preventing epithelial–mesenchymal transition and chemotherapy resistance.…”
Section: Epigenetic Drugs Combined With Chemotherapymentioning
confidence: 99%
“…Decitabine increased cisplatin's NOXA-mediated pro-apoptotic effect on breast cancer cell lines, demonstrating decitabine's good clinical potential in combination with cisplatin for the treatment of triple-negative breast cancers. 84 It has been shown that mitochondrial DNA depletion and low mitochondrial membrane potential can induce DNA methylation via DNMT and that zebularine inhibits epithelial–mesenchymal transition and improves chemotherapy sensitivity in mitochondrial DNA-depleted esophageal cancer cells. As a result, therapeutic strategies that increase the copy number of mitochondrial DNA and DNMT inhibitors may be useful in preventing epithelial–mesenchymal transition and chemotherapy resistance.…”
Section: Epigenetic Drugs Combined With Chemotherapymentioning
confidence: 99%
“…MCL-1 overexpression is one of the putative mechanisms of resistance to Venetoclax-based therapies in AML cells; hence, the Pev/5-Aza/Ven combination could be used as a novel therapeutic approach to overcome such Ven resistance. Notably, NOXA induction has been observed with decitabine in triple-negative breast cancer cells [ 44 ], enhancing the cytotoxic potential of cisplatin therapy in such cells.…”
Section: Ven–hma Synergy Mechanismsmentioning
confidence: 99%
“…Em linhagem MDA-MB-231, negativa para ER, o tratamento com 5-aza foi capaz de restaurar a expressão de receptores de estrógeno (SALAHUDDIN et al, 2022). Interessantemente, efeitos pró-apoptóticos mediados por cisplatina foram aumentados após tratamento em linhagens TNBC com decitabina (NAKAJIMA et al, 2022). Apesar desses significativos avanços, nem todas as linhagens de cânceres de mama respondem de modo similar, seja no tratamento com decitabina ou com a TSA.…”
Section: Discussionunclassified